Effect of Price, Promotion, and Brand Image on Purchasing Decision at PT. Agri Tepa Abadi - Ridho, Faisal; Gunawan, Rachmat; Yulianingsih (MultiTech Publisher, 2023)
This study aims to analyze and identify the effect of price, promotion and brand image both simultaneously and partially on purchasing decisions at PT Agri Tepa Abadi. The questionnaire was distributed to 100 respondents who were taken by proportional stratified random sampling with the population divided into 2 groups, namely 19 corporate consumer respondents and 81 end consumer respondents. The questionnaire was tested with a validity test, reliability test, and also classical assumption test. The results of these tests are valid, reliable, and can be used for regression data. The analysis method used in this research is descriptive and verification method with quantitative approach.